Potential of bamboo for energy purposes (Research, Society and Development, 2020)
Bamboo is a versatile, rapidly growing renewable raw material with high productivity, low handling cost, high ability to sequester atmospheric carbon and potential for energy purposes. The paper aimed to describe the potential of bamboo for energy purposes through different product alternatives. A specific literature review was carried out to tabulate data related to different energy alternatives for bamboo, considering the following questions: (i) which are the alternative bamboo products with energy potential? (ii) what are the parameters traditionally described in scientific articles? The average value of 4,396, 6,994, 4,597 and 4,530 kcal.kg-1, was found in the Gross Calorific Value (GCV) of biomass, charcoal, briquette and pellets of different bamboo species, values similar to those found for Eucalyptus grandis x Eucalyptus urophylla hybrid wood. The data prove the potential of bamboo as a source of energy and may even replace tree species traditionally used.